Using a pod as a platform Library-faculty collaboration - Eriksson, Fredrik (Septentrio Conference Series, 2020)
Universities tend to have two main tasks, namely research and education. Since 1999 the law that govern higher education in Sweden added a third task for the universities: to relate to their local environment. In other words they had to reach out with their research to the public. At the Philosophy department of the Humanities faculty at Lund University we had a meeting amongst the staff of the administration in 2016. Point of the discussion was the third task and how to reach out with our research. An idea, not too original, arose. What about starting a pod? After a few months of discussion regarding what it should contain, how to record and who should produce we were on our way. Fast forward 3 years we have recorded 30 episodes with philosophers on all levels on varying subjects such as Free Will, Epistemology and the Philosophy of Truth. To date we have over 15000+ listeners all over the world.  So why should a librarian engage in such activity? Well, first of all it’s a fantastic way to learn about your subjects and get to know your researchers. For the library it’s also meaningful to package research, sort it and make it available to people all over the world for a very, very long time. This with a minimal effort regarding time and resources.